Discourse vs. Practice of Governance and Innovation: the Masterplan for the 4th District of Porto Alegre - Fernanda Moscarelli; Geisa Bugs (Cahiers des Amériques Latines)
This article analyzes the gaps between the discourse on governance and innovation mobilized by decision-makers and stakeholders while elaborating the urban redevelopment plan for the 4th district of Porto Alegre (Brazil) and its practice. We used a combination of methods, including literature review, analysis of official and media-published documents, the collection of civil actors’ testimonies and our own participant observation. Our analyses reveal the adoption of international models, superficial participatory mechanisms and insufficient consideration of local conditions, raising concerns about persistent exclusion despite the rhetoric of innovation that supposedly surrounds it.